1999
DOI: 10.1080/03079459995019
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental model of bacterial chondronecrosis with osteomyelitis in broilers following exposure to Staphylococcus aureus by aerosol, and inoculation with chicken anaemia and infectious bursal disease viruses

Abstract: A series of experiments was designed in an attempt to reproduce bacterial chondronecrosis with osteomyelitis in broiler chickens using a natural route of infection. Birds in isolators were exposed to a suspension of Staphylococcus aureus by aerosol or exposed to S. aureus and subsequently inoculated with chicken anaemia virus (CAV) alone, or with CAV and infectious bursal disease virus (IBDV). Subsequently, S. aureus was recovered and bacterial chondronecrosis with osteomyelitis was diagnosed, by histology, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 23 publications
0
61
1
Order By: Relevance
“…No such macroscopic lesions were seen by sagittal sawing of the femoral bones. However, macroscopic lesions may be present in only 40% to 67% of cases, 7,11 and many osteomyelitic lesions are detectable only by histologic examination, 15 as in this case. The histologic findings in the proximal femur correspond to findings in staphylococcal and E coli osteomyelitis; however, chondronecrosis was not seen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…No such macroscopic lesions were seen by sagittal sawing of the femoral bones. However, macroscopic lesions may be present in only 40% to 67% of cases, 7,11 and many osteomyelitic lesions are detectable only by histologic examination, 15 as in this case. The histologic findings in the proximal femur correspond to findings in staphylococcal and E coli osteomyelitis; however, chondronecrosis was not seen.…”
Section: Discussionmentioning
confidence: 95%
“…However, no histologic description of bone was mentioned. This case illustrates that the absence of macroscopic bone lesions in lame chickens should encourage histopathologic and bacteriologic examination of the proximal part of both femur and tibiotarsus to confirm a diagnosis and prevent underdiagnosis, as described by Emslie et al 7 and McNamee et al 11 Osteomyelitis was histologically identified in the proximal femur of a lame chicken, and detection of gram-positive coccoid bacteria-as consistent with Enterococcus spp within the bone lesions and the pure culture of E hirae from the boneare reported for the first time, suggesting that E hirae was the cause of the osteomyelitic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed field gel electrophoresis has characterized this strain as the predominant type recovered from broilers with clinical disease in Northern Ireland . The CAV and IBDV strains used were CUX1 and G9, respectively (McNamee et al ., 1999).…”
Section: Methodsmentioning
confidence: 99%
“…aureus and virus strains. A S. aureus strain recovered from a naturally occurring case of BCO, designated Isolate 24, was used (McNamee et al ., 1999). Pulsed field gel electrophoresis has characterized this strain as the predominant type recovered from broilers with clinical disease in Northern Ireland .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation